Evaluation of the bleached human enamel by scanning electron microscopy - Miranda, Carolina Baptista [UNESP]; Pagani, Clovis [UNESP]; Benetti, Ana Raquel [UNESP]; Matuda, Fábio da Silva [UNESP] (Journal Of Applied Oral Science : Revista Fob, 2005)
Since bleaching has become a popular procedure, the effect of peroxides on dental hard tissues is of great interest in research. Purpose: The aim of this in vitro study was to perform a qualitative analysis of the human enamel after the application of in-office bleaching agents, using Scanning Electron Microscopy (SEM). Materials and Methods: Twenty intact human third molars extracted for orthodontic reasons were randomly divided into four groups (n=5) treated as follows: G1- storage in artificial saliva (control group); G2- four 30-minute applications of 35% carbamide peroxide (total exposure: 2h); G3- four 2-hour exposures to 35% carbamide peroxide (total exposure: 8h); G4- two applications of 35% hydrogen peroxide, which was light-activated with halogen lamp at 700mW/cm2 during 7min and remained in contact with enamel for 20min (total exposure: 40min). All bleaching treatments adopted in this study followed the application protocols advised by manufacturers. Evaluation of groups submitted to 35% carbamide peroxide was carried out after two time intervals (30 minutes and 2 hours per session), following the extreme situations recommended by the manufacturer. Specimens were prepared for SEM analysis performing gold sputter coating under vacuum and were examined using 15kV at 500x and 2000x magnification. Results: Morphological alterations on the enamel surface were similarly detected after bleaching with either 35% carbamide peroxide or 35% hydrogen peroxide. Surface porosities were characteristic of an erosive process that took place on human enamel. Depression areas, including the formation of craters, and exposure of enamel rods could also be detected. Conclusion: Bleaching effects on enamel morphology were randomly distributed throughout enamel surface and various degrees of enamel damage could be noticed. Clinical significance: In-office bleaching materials may adversely affect enamel morphology and therefore should be used with caution.

Desde o aumento da popularidade de tratamentos clareadores, o interesse em se pesquisar os efeitos dos peróxidos nos tecidos dentais duros é crescente. Proposta: O objetivo deste trabalho foi conduzir uma análise qualitativa in vitro do esmalte dental humano após clareamento com agentes para consultório, por meio de Microscopia Eletrônica de Varredura (MEV). Material e métodos: Foram utilizados 20 terceiros molares humanos hígidos, extraídos por motivos ortodônticos, sendo aleatoriamente divididos em 4 grupos (n=5) e tratados da seguinte forma: G1-armazenamento em saliva artificial (grupo controle); G2- 4 aplicações de peróxido de carbamida a 35% por 30 min (tempo total de aplicação: 2h); G3- 4 aplicações de peróxido de carbamida a 35% por 2 h (tempo total de aplicação: 8h); G4- 2 aplicações de peróxido de hidrogênio a 35%, que foi foto-ativado com lâmpada halógena a 700mW/cm2 por 7 min e mantido em contato com o dente durante 20 min (tempo total de aplicação: 40min). A avaliação dos grupos submetidos ao clareamento com peróxido de carbamida a 35% após 2 tempos de aplicação (30 minutos e 2 horas por sessão) para testar as situações extremas recomendadas pelo fabricante. As amostras foram recobertas com ouro para análise em MEV e foram examinadas utilizando 15kV e aumentos de 500x e 2000x. Resultados: Foram detectadas alterações morfológicas similares na superfície do esmalte após o clareamento com peróxido de carbamida a 35% e peróxido de hidrogênio a 35%. Porosidades e irregularidades caracterizando um processo erosivo foram observadas no esmalte humano. Áreas de depressão, incluindo a formação de crateras e exposição dos prismas de esmalte também foram observadas. Conclusão: Os efeitos do clareamento na morfologia do esmalte encontraram-se distribuídos aleatoriamente por toda a superfície do esmalte e danos em diferentes intensidades puderam ser evidenciados. Significância clínica: Agentes concentrados para clareamento em consultório podem comprometer a morfologia do esmalte e, portanto, devem ser utilizados com cautela.
Avaliação do esmalte dental humano submetido ao tratamento clareador por meio de Microscopia Eletrônica de Varredura
Keywords: Hydrogen peroxide; Carbamide peroxide; Tooth bleaching; Peróxido de hidrogênio; Peróxido de carbamida; Clareamento de dente